2020
DOI: 10.1101/2020.04.30.070532
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sex-specific vasopressin signaling buffers stress-dependent synaptic changes in female mice

Abstract: In many species, social networks provide benefit for both the individual and the collective. In addition to transmitting information to others, social networks provide an emotional buffer for distressed individuals. Our understanding about the cellular mechanisms that contribute to buffering is poor. Stress has consequences for the entire organism, including a robust change in synaptic plasticity at glutamate synapses onto corticotropin-releasing hormone (CRH) neurons in the paraventricular nucleus of the hypo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Excessive fear responses are characteristic of anxiety disorders and pave the way for a variety of other psychological and psychiatric problems. There is evidence from animal models that autonomic (1,2) and neural (2)(3)(4)(5) fear responses are reduced in the presence of a conspecific, a phenomenon known as social buffering (6)(7)(8). Adapting the paradigms that were used to study social buffering in animals, recent studies have shown similar social buffering of autonomic fear responses in humans (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…Excessive fear responses are characteristic of anxiety disorders and pave the way for a variety of other psychological and psychiatric problems. There is evidence from animal models that autonomic (1,2) and neural (2)(3)(4)(5) fear responses are reduced in the presence of a conspecific, a phenomenon known as social buffering (6)(7)(8). Adapting the paradigms that were used to study social buffering in animals, recent studies have shown similar social buffering of autonomic fear responses in humans (9,10).…”
Section: Introductionmentioning
confidence: 99%